The HOX-Apoptosis regulatory interplay in development and disease - Domsch, Katrin; Papagiannouli, Fani; Lohmann, Ingrid (Apoptosis and development, 2015)
Apoptosis is a cellular suicide program, which is on the one hand used to remove superfluous cells thereby promoting tissue or organ morphogenesis. On the other hand, the programmed killing of cells is also critical when potentially harmful cells emerge in a developing or adult organism thereby endangering survival. Due to its critical role apoptosis is tightly controlled, however so far, its regulation on the transcriptional level is less studied and understood. Hox genes, a highly conserved gene family encoding homeodomain transcription factors, have crucial roles in development. One of their prominent functions is to shape animal body plans by eliciting different developmental programs along the anterior-posterior axis. To this end, Hox proteins transcriptionally regulate numerous processes in a coordinated manner, including cell-type specification, differentiation, motility, proliferation as well as apoptosis. In this review, we will focus on how Hox proteins control organismal morphology and function by regulating the apoptotic machinery. We will first focus on well-established paradigms of Hox-apoptosis interactions and summarize how Hox transcription factors control morphological outputs and differentially shape tissues along the anterior-posterior axis by fine-tuning apoptosis in a healthy organism. We will then discuss the consequences when this interaction is disturbed and will conclude with some ideas and concepts emerging from these studies.
Gesehen am 23.06.2017